The Development and Evaluation of a Social Skills Group Training for Australian Adolescents on the Autism Spectrum - Afsharnejad, Bahareh (Curtin University, 2019)
Addressing a current lack of evidence-based interventions targeting the social skills of Australian autistic adolescents, this thesis undertook a holistic adolescent-centric approach in investigating the efficacy of a social skills group training, KONTAKT®. This thesis concluded that compared to an active control cooking group, explicit social skills group training was more efficacious in improving Australian autistic youth’s social outcomes. This thesis further highlighted that methodologically rigours research in a community-based setting is possible.